## All Definition at its Root is: ((A --> A) --> (B <--> -A))

What is the basis for reason? And mathematics?

Moderators: AMod, iMod

Eodnhoj7
Posts: 5880
Joined: Mon Mar 13, 2017 3:18 am

### All Definition at its Root is: ((A --> A) --> (B <--> -A))

All definition, as the progression of one assumption to another, can be expressed under the equation:

((A --> A) --> (B <--> -A))

All is Recursive/Inversive Contexts.

1. All assumptions are contexts: (A)(B)(-A)
2. All assumptions are recursive: (A --> A)
3. All assumptions are isomorphic: (A --> A) --> (B <--> -A)****
4. All assumptions are contexts: ((A-->A)-->(B<-->-A))

****If "A" is cat and cat directs to Dog "B", as non cat, the recurssion of variables in Dog, as cat, occurs (such as hair, teeth, 4 legs, etc.), but the Dog is not cat. So if Cat progresses to Dog, Dog and Not Cat occurs through eachother.

The same occurs numerically where 1-->2 shows the difference of 1 where if 1 is subtracted, -1, 2 reverts back to one again.

As to one and many, first there was only cat then dog occurs resulting in many contexts. 1=Cat. Many (2) = Dog and Cat.

Everytime a context progresses to another context, the new context contains elements of the old (through recursion) but the new context is not the old context and contains what the prior context is not. Thus the new context always contains an absence of the old context in one respect, due to newness of the context, while contains elements of the old at the same time.

This trinitarian nature to definition is further reflected, under a trinity of contexts,
as one context ( ),

((A-->A)-->(B<-->-A))

### Who is online

Users browsing this forum: No registered users and 34 guests